2021
DOI: 10.1002/cssc.202102053
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Nitration with Nitrite

Abstract: Scheme 1. Selected approved drugs containing nitro functionalities.Scheme 2. Traditional approach (electrophilic aromatic substitution) in comparison to the electrochemical nitration with nitrite (this work); C gr = graphite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 96 publications
1
15
0
2
Order By: Relevance
“…222 In 2021, the Waldvogel group showed that tetrabutylammonium nitrite is also a safe NO 2 source in the electrochemical nitration of aromatic compounds 388 (Scheme 107). 223 The reaction proceeded mainly with electron-rich arenes; the yields were significantly dependent on the na-ture of the substrate. According to the postulated mechanism, initial anodic oxidation of nitrite to NO 2 , which is in equilibrium with N 2 O 4 , takes place.…”
Section: Organic Nitritesmentioning
confidence: 99%
“…222 In 2021, the Waldvogel group showed that tetrabutylammonium nitrite is also a safe NO 2 source in the electrochemical nitration of aromatic compounds 388 (Scheme 107). 223 The reaction proceeded mainly with electron-rich arenes; the yields were significantly dependent on the na-ture of the substrate. According to the postulated mechanism, initial anodic oxidation of nitrite to NO 2 , which is in equilibrium with N 2 O 4 , takes place.…”
Section: Organic Nitritesmentioning
confidence: 99%
“…Therefore, we are quite interested in the possibility of developing a new nitration reagent based on this hoststructure. The preparation of dinitro-5,5-dimethylhydantoin (DNDMH, 11) was readily achieved by the treatment of 5,5dimethylhydantoin (12) with ammonium nitrate and trifluoroacetic anhydride (Scheme 1). And the structure of 11 was unambiguously determined through X-ray crystallography (CCDC 2252101).…”
mentioning
confidence: 99%
“…Using the traditional conditions, the mixed nitric–sulfuric acid presents distinct disadvantages of inferior functional group tolerance, poor position selectivity, and formation of byproducts from oxidation or hydrolysis . In recent decades, divergent strategies for nitration of arenes have been developed, which include oxidation of aryl azides or anilines, ipso -nitration of prefunctionalized arenes, transition metal catalyzed cross-coupling, directed C–H activation, electrochemical, photochemical, and enzymatic nitrations …”
mentioning
confidence: 99%
“…15 Hexafluoroisopropanol (HFIP) also shows excellent performance in electrophilic nitration reactions. 16 For example, Hua and co-workers developed a simple nitrating system for the nitration of arenes at room temperature by using 1 equiv of nitric acid in HFIP (Scheme 1d). 17 The solvent HFIP can be easily recycled, and the only byproduct is water.…”
mentioning
confidence: 99%